Śrīśrīyugācāryya-jībana-carita : saṅghanetā Ācāryya Śrīmaṯ Svāmī Praṇabānandajīra jībana-carita - Bedānanda, Swami (Bhārata Sebāśrama Saṅgha, 1978)
Biography of Swami Pranavananda, 1896-1941, founder of the Hindu socioreligious organization Bharat Sevasram Sangha.